여주지역 영유아 대상 영양플러스 사업 효과 - 영유아 영양보충 및 보호자 영양교육 실시에 따른 영유아의 영양개선효과를 중심으로 - 박옥진; 이민준; 김지향; 민성희; 이현숙; Park, Ok-Jin; Lee, Min-June; Kim, Ji-Hyang; Min, Sung-Hee; Lee, Hyun-Sook (Korean journal of community nutrition, 2009)
This study evaluated the effect of nutritional improvement of 0~5 year children of financially poor families after nutrition supplement of children and nutrition education in parents/guardians. The subject selected among applicants for low-income family financing of the government included 198 children (0~12 months:92, 1~5 years:106), and the average ages were 5.3 months and 2.4 years respectively. Food that includes each nutrient factor was provided to the subject for six months. Nutrition education was performed in two ways, through class and private education, once a month for both. Nutritional improvement was evaluated by body measurement and anemia prevalence rate. As to the survey on breast-feeding, complete breast-feeding accounted for 58.7%, weaning food 27.3%, and combined feeding 14.1% respectively, which shows that breast-feeding accounted for the largest percentage. The education program improved knowledge and attitude of the parents/guardians, which brings in positive effects on growth of children as well. The nutrition knowledge score was improved after nutrition education in 0~12 month children $(8.5±1.75\;to\;8.9±1.69)$ and 1~5 year children $(7.3±1.39\;to\;7.8±1.30)$. The nutrition attitude score was significantly improved in 0~12month children $(52.0±6.99$ to $53.5±5.21$, p < 0.001) and 1~5year children ($45.1±7.30$ to $49.0±5.96$, p < 0.001). In evaluation on nutritional improvement based on body measurements, it turned out that the wasting was reduced as for children in consideration of the height and weight according to the subject's age. The concentration of hemoglobin after the nutrient treatment for six months was significantly improved, and the anemia prevalence rate as well was reduced from 40.6% to 13.5%, which indicates the significant improvement. Based on the findings above, it turned out that providing quality food to children and nutrition education to the parents/guardians poorly fed in low-income families improved knowledge and attitude of the guardians and prevents anemia and improves growth, which brings in positive effects on growth of children. In the results regarding attitude and knowledge on nutrient/dietary life; however, the improvement level was relatively low when the extent before the education was too small, which indicates the need to revise and complement the contents and methods. In addition, as shown in the result of body measurement, long-term and consistent investigation is necessary since it is difficult to judge the effect on growth only based on short-term nutrient supplement.